X-Ray Diffraction Studies of Low to High Temperature Synthesis of LiMn₂O₄ - N, Kamarulzaman; M.R, Muhamad; A.K, Arof (Malaysian Journal of Science, 2002)
LiMn₂O₄ is prepared from acetates of lithium and manganese using the sol-gel method. The precursor obtained was annealed at different temperatures for 24 hours and furnace cooled. The materials were then grounded into very fine powder. X-Ray Diffraction measurements are done on the materials and the spectrograms are analyzed for identification, purity and crystallinity studies.